News of Organizations and Institutions (Academy of Management Journal, 1964)
The article presents news briefs concerning organizations and institutions in the U.S. as of December 1964. Top level military and civilian authorities on automatic data processing concluded an intensive three-day Automatic Data Processing Systems Seminar on September 17. A Systems Science Laboratory to be opened in New York University’s School of Engineering and Science in September will enable industrial engineering and operations research students to diagnose and experiment with the impact of modern technology on man and industry. A new department of Training Materials for Industry has been established at the Bureau of Industrial Relations, University of Michigan.